O silêncio nos westerns dos diretores Sergio Leone e Clint Eastwood - GOMES, Delson de Matos (2016)
When put side by side, the western movies directed by Sergio Leone and Clint Eastwood both have similarities and differences in their construction (montage), in which Leone influences the American director about using the cinematographic silence to create different climates and sensations. The silence on the cinematographic field has great semantic value and dramatic potential to be explored and when it is combined with the western genre, it shows through characteristic sounds and images from this genre. The present research aims to identify and discuss the occasions in which the different types of silence occur in the western movies from the directors previously mentioned and observe the similarities and the differences of those constructions and uses by the filmmakers. In the present analysis, the following works by Sergio Leone were used: A Fistful of Dollars (1964), For a Few Dollars More (1965), The Good, the Bad and the Ugly (1966) and, Once Upon a Time in the West (1968), in which three of them Clint Eastwood acted under direct influence from the Italian director, in his way of acting as a form of performing the genre as a director. The following analyzed works by Clint Eastwood were: High Plains Drifter (1973), The Outlaw Josey Wales (1976), Pale Rider (1985), and Unforgiven (1992).